1959
DOI: 10.1002/aic.690050203
|View full text |Cite
|
Sign up to set email alerts
|

Mass transfer at low flow rates in a packed column

Abstract: Mass transfer in packed columns has been investigated for a variety of column and packing sizes but at flow rates restricted to fully developed turbulent conditions. The present work was undertaken to investigate mass transfer at flow-rate conditions in the transition and laminar regions.A dual treatment of experimental data required a knowledge of the variation of concentration and velocity with radial position. A tracer-injection technique was employed which consisted in the introduction of a tracer gas into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0
1

Year Published

1962
1962
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(22 citation statements)
references
References 3 publications
4
17
0
1
Order By: Relevance
“…As illustrated in Figure 8-1 velocity ratios greater than 100% can occur for columnto-particle diameter ratios less than 10 and beyond ~50 the impact is negligible. Also shown in Dorweiler and Fahien (1959) performed similar experiments that agreed with Schwartz and Smith (1953) and went to flowrates as low as 30 cm/min. In a later study by Fahien and Smith (1955) significant radial effects were observed for column-to-particle diameters less than 20.…”
Section: Radial Flow Maldistributionsupporting
confidence: 50%
“…As illustrated in Figure 8-1 velocity ratios greater than 100% can occur for columnto-particle diameter ratios less than 10 and beyond ~50 the impact is negligible. Also shown in Dorweiler and Fahien (1959) performed similar experiments that agreed with Schwartz and Smith (1953) and went to flowrates as low as 30 cm/min. In a later study by Fahien and Smith (1955) significant radial effects were observed for column-to-particle diameters less than 20.…”
Section: Radial Flow Maldistributionsupporting
confidence: 50%
“…10,11) The basic differential equation for mass transfer, which considers diffusion in the radial direction only and bulk flow in the axial direction, is written as Eq. (1) 6.…”
Section: Discussionmentioning
confidence: 99%
“…A way to improve the pseudo‐homogeneous approach is to take into account the effect of the radial distribution of packing porosity on the overall heat‐transfer properties. Several hydrodynamic investigations were carried out 30 or 40 years ago by laser velocimetry or by hot‐wire anemometry,57–59 but the measurements were made at the outlet of the packing. The velocity profile depends greatly on the clearance, and the radial fluctuation of the velocity was smoothed and showed only one peak close to the wall.…”
Section: Heat‐transfer Modelsmentioning
confidence: 99%